2012
DOI: 10.1016/j.bbadis.2012.08.005
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin affects the circadian clock and metabolic rhythms in a tissue-specific manner

Abstract: Metformin is a commonly-used treatment for type 2 diabetes, whose mechanism of action has been linked, in part, to activation of AMP-activated protein kinase (AMPK). However, little is known regarding its effect on circadian rhythms. Our aim was to evaluate the effect of metformin administration on metabolism, locomotor activity and circadian rhythms. We tested the effect of metformin treatment in the liver and muscle of young lean, healthy mice, as obesity and diabetes disrupt circadian rhythms. Metformin led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 52 publications
3
38
2
1
Order By: Relevance
“…Insulin targets, such as fat, liver and muscle, function as metabolic rheostats and depend on cell-autonomous clock function. Existing first-line drug therapies for metabolic disease and type 2 diabetes, such as the commonly used insulin sensitiser, metformin, are known to modulate molecular clock function in insulinsensitive tissues [166][167][168]. Sleep disturbances predispose individuals to obesity and diabetes, and obesity predisposes individuals to sleep disturbances, instigating a vicious cycle [18,169].…”
Section: Therapeutic Agentsmentioning
confidence: 99%
“…Insulin targets, such as fat, liver and muscle, function as metabolic rheostats and depend on cell-autonomous clock function. Existing first-line drug therapies for metabolic disease and type 2 diabetes, such as the commonly used insulin sensitiser, metformin, are known to modulate molecular clock function in insulinsensitive tissues [166][167][168]. Sleep disturbances predispose individuals to obesity and diabetes, and obesity predisposes individuals to sleep disturbances, instigating a vicious cycle [18,169].…”
Section: Therapeutic Agentsmentioning
confidence: 99%
“…The exclusion of diabetic patients have been mainly due to the use of metformin since AMP activated protein kinase (AMPK) activators were shown to regulate the pattern of clock genes [11], [12], [13], [14]. Subjects receiving hormones (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The results of a study involving mice showed that metformin causes phase advance in the liver, but phase delay in muscle 53 , and the effects of metformin on circadian rhythm are blocked in mice with knock-out of Prkaa2, the gene encoding AMPK subunit α2 (REF. 52).…”
Section: Key Pointsmentioning
confidence: 99%
“…Metformin also affects the circadian control of glucose metabolism in liver and muscle 42 . Metformininduced AMPK activation results in phosphorylation of casein kinase I, which leads to degradation of the circadian clock component mPer2, thereby increasing expression of the CLOCK and BMAL1 circadian genes and causing phase advance in the circadian rhythm in treated rodents, compared with untreated controls 52,53 .…”
Section: Key Pointsmentioning
confidence: 99%